2022
DOI: 10.5194/tc-16-4305-2022
|View full text |Cite
|
Sign up to set email alerts
|

Observed mechanism for sustained glacier retreat and acceleration in response to ocean warming around Greenland

Abstract: Abstract. The dynamic loss of ice via outlet glaciers around the Greenland Ice Sheet is a major contributor to sea level rise. However, the retreat history and ensuing dynamic mass loss of neighboring glaciers are disparate, complicating projections of sea level rise. Here, we examine the stress balance evolution for three neighboring glaciers prior to; at the onset of; during; and, where possible, after retreat. We find no dynamic or thickness changes preceding retreat, implicating a retreat trigger at the ic… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 63 publications
1
8
0
Order By: Relevance
“…In PI, it has been suggested that 98% of the surface velocities are due to basal slip (Collao-Barrios et al, 2018). Depth-integrated resistive stresses are estimated with a stress exponent of n = 3 and a viscosity rate factor of B = 300 kPa yr 1/3 , similar to that used in previous investigations (Carnahan et al, 2022;Van Der Veen et al, 2011). The driving stress in the x-direction takes the form:…”
Section: Changes In Force Balancementioning
confidence: 98%
See 4 more Smart Citations
“…In PI, it has been suggested that 98% of the surface velocities are due to basal slip (Collao-Barrios et al, 2018). Depth-integrated resistive stresses are estimated with a stress exponent of n = 3 and a viscosity rate factor of B = 300 kPa yr 1/3 , similar to that used in previous investigations (Carnahan et al, 2022;Van Der Veen et al, 2011). The driving stress in the x-direction takes the form:…”
Section: Changes In Force Balancementioning
confidence: 98%
“…In our research, we use the force balance method according to van der Veen & Whillans (1989), which provides us with the stress balance in glaciers for a given instant. The force balance method has been used extensively in Greenland (Carnahan et al, 2022) to understand glacier behavior, either individually (Van Der Veen et al, 2011) or on multiple glaciers for given periods (Bartholomaus et al, 2016;Stearns and van der Veen, 2018;Van Der Veen et al, 2011;Enderlin et al, 2018; https://doi.org/10.5194/egusphere-2024-1053 Preprint. Discussion started: 14 May 2024 c Author(s) 2024.…”
Section: Changes In Force Balancementioning
confidence: 99%
See 3 more Smart Citations